Common Aspects of Anna Akhmatova’s and Marina Tsvetayeva’s Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides information about the works of Russian poets. The lyrical heritage and poetic world of artists are analyzed. A reaction to the skillful depiction of female soul experiences in his poems.